2017
DOI: 10.3748/wjg.v23.i3.414
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of immunomonitoring in the treatment of inflammatory bowel disease

Abstract: Despite improvement in outcomes, loss of response (LOR) to tumor necrosis factor-alpha (TNFα) therapies is a big concern in the management of inflammatory bowel disease. LOR is associated with flares of disease, increased hospitalisation rates, need for surgical interventions, and decline in quality of life. LOR may be multifactorial, but immunogenicity makes a significant contribution. Traditionally doses of anti-TNFα have been adjusted based on clinical response, using a standard approach. Immunomonitoring i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…However, no official recommendation exists about the optimal range of TL to maintain clinical remission. In addition, the consequences of TL measurements, including dosing or time interval adaptation of the biological, change of the biological, and addition or alterations of immunomodulatory treatments, have only been described in a few studies [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…However, no official recommendation exists about the optimal range of TL to maintain clinical remission. In addition, the consequences of TL measurements, including dosing or time interval adaptation of the biological, change of the biological, and addition or alterations of immunomodulatory treatments, have only been described in a few studies [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Current evidence suggests that there may be clinical benefit to monitoring of drug troughs and antibody levels during treatment with TNFα inhibitors. [10] Whether infliximab at high-dose is more effective than adalimumab at regular dose, as suggested by our case, remains unclear. Increasing the dose of infliximab has previously shown to be efficacious in inducing remission of intestinal BD.…”
Section: Discussionmentioning
confidence: 76%
“…The mechanism of loss of response to TNFα inhibitors is thought to be secondary to the formation of antibodies to the medication, which leads to either blocking of the drug activity or faster drug clearance as evidenced by lower drug trough levels. [10] In patients treated with Infliximab for inflammatory bowel diseases, antibodies against the medication form in a significant proportion of patients with nearly 30% requiring adjustments to their treatment. [11] Current evidence suggests that there may be clinical benefit to monitoring of drug troughs and antibody levels during treatment with TNFα inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvement in clinical outcome, loss of response to anti‐TNF‐α Mabs remains a major concern in the management of IBD patients. Increasing evidences suggested that therapeutic drug monitoring (TDM) of anti‐TNF‐α Mabs could help to improve remission rate or mucosal healing achievement but the clinical interest of TDM of anti‐TNFα Mabs in IBD patients remains to be further demonstrated . One of the limitations lies in the absence of standardization of the analytical methods used to measure IFX plasma concentration.…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations lies in the absence of standardization of the analytical methods used to measure IFX plasma concentration. Indeed, up to now, all previous studies used enzyme‐linked immunosorbent assay (ELISA) or homogeneous mobility shift assay, but the systematic bias and lack of specificity of some ELISA methods could be of major concerns, and lead to the determination of different clinically relevant IFX thresholds or different therapeutic strategies .…”
Section: Introductionmentioning
confidence: 99%